Partisipasi Masyarakat Dalam Pesta Demokrasi Tahun 2024 Kota Batam - Banjarnahor, Haposan; Husda, Anggun Permata; Ompusunggu, Hermaya; Rustam, Triana Ananda (LPPM Universitas Putera Batam, 2024)
The results of the 2024 Election were determined by the Indonesian General Election Commission (KPU) on Wednesday, March 20, 2024. The determination of the results of the 2024 Election was stated in KPU Decree Number 360 of 2014 on Determination of the Results of the Presidential and Vice Presidential Elections, Members of the People's Representative Council, Regional Representative Council, Provincial People's Representative Council, and Regency/City People's Representative Councils nationally in the 2024 General Election.